先化简再求值:4(a+b)²-7(a+b)²+(a+b)²其中a=-2分之1,b=-3
1个回答
4(a+b)²-7(a+b)²+(a+b)²
=(4-7+1)(a+b)²
=-2(a+b)²
=-2(-1/2-3)²
=-2x49/4
=-49/2
=-24.5
相关问题
先化简,再求值:a^2+a-b^+b分之a^2-a-b^2-b,其中a=4分之3,b=4分之1
先化简.再求值 7a(a+b)-3b(a+b)其中 a=2/7 b=2/3
先化简,再求值:a分之a^2-b^2/(a-a分之2ab-b^2),其中a=-3,b=4
先化简,再求值:(a-b)(a-2b)-(3a-2b)(a-3b),其中a=4,b=-1
先化简,再求值:a^3*(-b^3)^2+(-2分之1ab^2)^3,其中a=4分之1,b=4
1.先化简再求值:(a+2b)(2a-b)-(a+2b)²-(-a-2b)²,其中a=四分之一,b=
先化简,再求值:(3a+2b)(2a-3b)-(a-2b)(2a-b),其中a=-1.5,b=四分之一.
先化简再求值:(a-b)(a²+ab+b²)+b²(b+a)-a³,其中a=-1/4,b=2 .
先化简,再求值:b^4+(-a-b)(-a+b)(a^2+b^2),其中:a=-1,b=2011.
先化简,再求值:a+2b/a+b+2b²/a²-b²,其中a=-2,b=3/1